Production, functional stability, and effect of rhamnolipid biosurfactant from Klebsiella sp. on phenanthrene degradation in various medium systems - Ahmad, Zulfiqar; Zhang, Xuezhi; Imran, Muhammad; Zhong, Hua; Andleeb, Shaista; Zulekha, Rabail; Liu, Guansheng; Ahmad, Iftikhar; Coulon, Frederic (Elsevier, 2020)
The present study investigated the stability and efficacy of a biosurfactant produced by Klebsiella sp. KOD36 under extreme conditions and its potential for enhancing the solubilization and degradation of phenanthrene in various environmental matrices. Klebsiella sp. KOD36 produced a mono-rhamnolipids biosurfactant with a low critical micelle concentration (CMC) value. The biosurfactant was stable under extreme conditions (60 °C, pH 10 and 10% salinity) and could lower surface tension by 30% and maintained an emulsification index of > 40%. The emulsion index was also higher (17–43%) in the presence of petroleum hydrocarbons compared to synthetic surfactant Triton X-100. Investigation on phenanthrene degradation in three different environmental matrices (aqueous, soil-slurry and soil) confirmed that the biosurfactant enhanced the solubilization and biodegradation of phenanthrene in all matrices. The high functional stability and performance of the biosurfactant under extreme conditions on phenanthrene degradation show the great potential of the biosurfactant for remediation applications under harsh environmental conditions.
Keywords: Mono-rhamnolipids; Klebsiella sp.; Biodegradation; Emulsification index; Surface tension; Hydrocarbons